Inside Back Cover: Synthesis of Polysubstituted γ‐Butenolides via a Radical Pathway: Cyclization of α‐Bromo Aluminium Acetals and Comparison with the Cyclization of α‐Bromoesters at High Temperature (Chem. Eur. J. 32/2015). Issue 32 (23rd July 2015) - Bénéteau, Romain; Despiau, Carole F.; Rouaud, Jean‐Christophe; Boussonnière, Anne; Silvestre, Virginie; Lebreton, Jacques; Dénès, Fabrice
Abstract : Polysubstituted γ‐butenolides were obtained by a one‐pot sequence that involves the radical cyclization of α‐bromo aluminium acetals under mild reaction conditions, followed by in situ oxidation. In their Full Paper on page 11378 ff. F. Dénès et al. compare this approach with the direct cyclization of α‐bromoesters at high temperature, for which side reactions were observed. Among these, hydrogen‐atom transfer (HAT) from the side‐chains, which have remained so far unnoticed during this type of cyclization, were brought to light by the epimerization of "unreactive" stereogenic centres.